2020
DOI: 10.1186/s43055-020-00220-3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis: correlation between lung abnormalities on high-resolution computed tomography (HRCT) and pulmonary function tests (PFTs)

Abstract: Background Systemic sclerosis is a connective tissue disease that affects multiple systems and causes fibrosis of the skin and internal organs. There are two ways in which the lungs can be involved in patients with systemic sclerosis, either isolated pulmonary hypertension or interstitial lung fibrosis. The purpose of this study is to correlate the high resolution CT findings with pulmonary function tests in patients with systemic sclerosis to evaluate the severity of lung changes. Results Significant inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…2 Of three patients who could not perform PFT, two had a UIP pattern with honey-combing suggesting severe disease associated with honey-combing and coarse reticular fibrosis. This was in agreement with the observations of Ooi et al 7 Traction bronchiectasis was seen in 14 (38.8%) cases in our study, in contrast with Ibrahim et al 23 . In almost all the patients in our study, lower lobe predominance of ILD was observed.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…2 Of three patients who could not perform PFT, two had a UIP pattern with honey-combing suggesting severe disease associated with honey-combing and coarse reticular fibrosis. This was in agreement with the observations of Ooi et al 7 Traction bronchiectasis was seen in 14 (38.8%) cases in our study, in contrast with Ibrahim et al 23 . In almost all the patients in our study, lower lobe predominance of ILD was observed.…”
Section: Discussionsupporting
confidence: 94%
“…Similar observations, were reported by other workers. 23,25 Mediastinal lymphadenopathy was found in seven (19.4%) cases in our study while Bhalla et al 26 and Ibrahim et al 23 observed in 60% and 76.7% of their patients, respectively.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation